The Design of Computer Forms for Tropical Medical Research - Byass, P. (Methods of Information in Medicine, 1986)
The design of forms for recording medical research data in the field is discussed in the light of the computer hardware and software to be used for their subsequent analysis. In particular, the principles of relational database management systems are extrapolated to the structure of forms. Specific issues of subject identification, layout of forms, different types of data and coding methods are developed. Finally, the special problems of applying these principles in the tropics, and experiences of so doing, are considered.
Keywords: Computer Forms; Relational Databases; Identification; Coding; Tropics